2010
DOI: 10.5004/dwt.2010.1284
|View full text |Cite
|
Sign up to set email alerts
|

Industrial water reuse with integrated membrane system increases the sustainability of the chemical manufacturing

Abstract: ab s t r ac tThe DECO water treatment facility (built and operated by Evides Industriewater B.V.) is using an integrated membrane system to produce demineralised water for the production facilities of Dow Benelux B.V in Terneuzen, the Netherlands. The system consists of large-scale continuous microfi ltration (CMF) unit and two-pass reverse osmosis (RO) unit with FILMTEC TM membranes. It is the fi rst time in the Netherlands that domestic waste water is re-used in such a large scale for industrial use. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Van Paassen et al then showed that biofouling accumulated on feed spacers causes an exponential increase in the pressure drop across the membrane module containing the feed spacer [ 147 ]. To remedy the biofouling of feed spacers, various solutions have been proposed [ 148 , 149 ]. More recently, researchers have focused on the surface chemistry of the feed spacers.…”
Section: Anti-fouling Methods and Materialsmentioning
confidence: 99%
“…Van Paassen et al then showed that biofouling accumulated on feed spacers causes an exponential increase in the pressure drop across the membrane module containing the feed spacer [ 147 ]. To remedy the biofouling of feed spacers, various solutions have been proposed [ 148 , 149 ]. More recently, researchers have focused on the surface chemistry of the feed spacers.…”
Section: Anti-fouling Methods and Materialsmentioning
confidence: 99%
“…Compared to SW fodder, plant recovery increased by 20%, saving on 3 million m3 / a water intake. Reduced water intake helps reduce the use of active chemicals [36]. The fact that burnt clay sludge sludges absorb significantly more water than normal dense aggregates is mainly due to their cohesive cellular structure and the size of the pores.…”
Section: Water Reuse Treatmentmentioning
confidence: 99%
“…Another advantage of membrane processes is that they can flexibly be scaled up with different unit operations and membrane types to add treatment capacity if necessary (Quist-Jensen et al 2015). Various full-scale studies have demonstrated that membrane-based advanced treatment processes (MATP) can be designed to reclaim WWTP effluents for all three water usage types: (i) (in)direct potable reuse for domestic consumption (Ortuño et al 2012;Chalmers & Patel 2013;Van Houtte & Verbauwhede 2013), (ii) demineralised process water for industrial reuse (Majamaa et al 2010;Shang et al 2011) and (iii) irrigation water for agricultural reuse (Hamoda et al 2015).…”
Section: Introductionmentioning
confidence: 99%